(untitled) (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
This research explores the definition of soft skills in engineering education literature and suggests a new framework for understanding the components of soft skills. The study reveals that there is a lack of consensus on what constitutes soft skills and how best to define the term in an engineering education context. The work also highlights the importance of a mutual understanding of the concepts shaping engineering soft skills to ensure meaningful measurement and attainment of competencies. The study aims to pave the way to develop relevant pedagogical interventions and assessment tools for engineering soft skills. The research methodology used in this work is a content analysis on reviewed citations, which extracts explicit definitions and components of soft skills in 93 reviewed publications. We conclude that a precise distinction between knowledge, attitude, personality traits, and skills is necessary to develop engineering soft skills further and align the expectations of the profession and engineering higher education institutions.